Identification of Natural Resource-Based Economic Potential around New Indonesian Capital - Zulfikar, Akbar Lufi; Mahardika, Swadia Gandhi; Maulana, Indra; Swandari, Selly (Economic and Business Horizon, 2024)
The purpose of the study was to identify the potential of natural resource-based economy in the buffer zone of the national capital (Samboja District, Kutai Kartanegara Regency and to determine the readiness of Kutai Kartanegara Regency in terms of natural resource-based economic potential that can be developed as a buffer zone of the national capital. The study was a desk study using quantitative methods. Researchers focused on literature studies, observations, collection, processing and processing of secondary data and analyzed using the SWOT method. The results of the study showed that Samboja District has abundant natural resource potential but its utilization is not optimal, with economic contributions still dominated by certain sectors. The development of a natural resource-based economy needs to be balanced with infrastructure development, improving the quality of human resources, and ongoing attention from the government to ensure environmental sustainability.